1997
DOI: 10.7883/yoken1952.50.123
|View full text |Cite
|
Sign up to set email alerts
|

The Latest Seroepidemiological Pattern of Hepatitis a in Japan

Abstract: SUMMARY:Age-specific prevalence of anti-hepatitis A virus antibody (anti-HAV) was surveyed with 2,708 sera collected in 1994 in various areas of Japan. By age-group analyses, we found strong association of anti-HAV antibody with higher. age group. The prevalence ratios of antibody in the groups of 30-34, 35-39, 40-44, 45-49, 50-54, 55-59, 60-64 and 65 years or older were 0, 4.2, 22.0, 44.8, 57.6, 76.4, 84.5 and 91.4%, respectively.Geometric mean titers of anti-HAV antibody in the positive age groups were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 14 publications
2
21
0
1
Order By: Relevance
“…The age-speci®c prevalence pattern of HAV observed in this cross-sectional study is similar to that reported previously in the United States, Australia, Japan, and northern and western European countries [Bottiger et al, 1997;Kiyohara et al, 1997;Ferson et al, 1998;CDC, 1999]. Because of the presence of subclinical cases and the need for con®rmatory testing by serology, under diagnosis is likely.…”
Section: Discussionsupporting
confidence: 86%
“…The age-speci®c prevalence pattern of HAV observed in this cross-sectional study is similar to that reported previously in the United States, Australia, Japan, and northern and western European countries [Bottiger et al, 1997;Kiyohara et al, 1997;Ferson et al, 1998;CDC, 1999]. Because of the presence of subclinical cases and the need for con®rmatory testing by serology, under diagnosis is likely.…”
Section: Discussionsupporting
confidence: 86%
“…In Japan, there was rapid improvement in sanitary conditions and standards of living after World War II, and clean public water systems were introduced in the 1950s. Surveys from across the country reported that the age at which more than half of the population had HAV antibodies was above 30 years in the 1970s [Moritsugu et al, 1978;Ichida et al, 1981] and has been increasing [Kiyohara et al, 1997;Furusyo et al, 1998]. The present study revealed that the age at which more than half of the hemodialysis patients and healthy individuals (medical staff members) who were positive for anti-HAV (total), was both above 60 years.…”
Section: Discussionmentioning
confidence: 44%
“…Total anti-HAV antibody was determined for all specimens using an inhibition enzyme linked immunosorbent assay (ELISA) as described (12). Briefly, purified inactivated HAV (KRM003 strain, genotype IIIB) was bound to microtiter plates (Nunc, F96 CERT.MAXISOAP, Denmark) coated with anti-HAV rabbit serum (HAV-plates).…”
Section: Methodsmentioning
confidence: 99%